Silver Nanoparticles (AgNPs) Act as Nanoelicitors in Melissa officinalis to Enhance the Production of Some Important Phenolic Compounds and Essential Oils - Coskun, Yasemin; Kapdan, Goncagul (Flavour and fragrance journal, 2025)
ABSTRACT Nanoparticles (NPs) are well‐known biostimulants in plant biotechnology, utilised to enhance the physical properties of plants and exhibit positive effects on them. The important key role is the most suitable type, effective dose and size of NP to be used in plant tissue culture systems. In this study, various concentrations of silver nanoparticles (AgNPs; 0, 25, 50, 75 and 100 μg L−1) were tested as elicitors in callus culture with the aim of enhancing secondary metabolite production in lemon balm (Melissa officinalis L.). According to the results obtained, callus formation rates have shown an increase in all applications compared to the control group. The highest callus formation, weight and diameter were observed in 50 μg L−1 application. In this application, the callus structure was compact and its colour was green. However, the aromatic compounds, neral and geranial increased significantly in 25 μg L−1 application. The maximum increase in phenolic compounds such as caffeic acid, chlorogenic acid, proto‐catechic acid, hesperidin and p‐coumaric acid was observed in the 75 μg L−1 AgNP and the highest increase in rosmarinic acid compound was determined in the 50 μg L−1 application. The study found that AgNP applications are an effective method for increasing the production of secondary metabolites in medicinal and aromatic plants, such as lemon balm, in vitro. Silver nanoparticles (AgNPs) stimulate the accumulation of important aromatic compounds, neral and geranial in lemon balm leaf callus cultures. The valuable phenolic compound rosmarinic acid is highly affected by the application of 50 μg L−1 AgNP. The study strongly indicates that NPs in plant culture systems can increase the production of secondary metabolites in medicinal and aromatic plants like lemon balm.